An Imperial, National and State Debate: The Rise and Near Fall of the Australian Forestry School, 1927-1945. (1st May 2009) - Bennett, Brett
Abstract : A variety of debates that surrounded the opening of the Australian Forestry School at Canberra in 1927 illuminate the divergent beliefs about forestry education and conservation policy that many British imperial and Australian foresters and politicians held during the 1910s-1940s. A controversial English-born forester, Charles Edward Lane Poole, lobbied for the School's creation and headed it for many years. The Commonwealth Government supported the School throughout the 1920s-1940s amidst a variety of financial hardships and state criticisms. Many leading foresters throughout the British Empire who were born outside of Australia supported the School. But many professionally trained foresters and Australian politicians who had been born in Australia were more ambivalent or critical of the School. This article traces these contentious debates throughout the years leading up to and following the creation of the Australian Forestry School.